(untitled) (Swiss Medical Weekly, 2012)
PRINCIPLES: In Switzerland, more and more patients go directly to the emergency department, bypassing general practitioners. However, a mixture of non-urgent walk-in patients and acute emergencies in the same emergency department can inevitably make it more difficult to provide genuine emergencies with rapid treatment, leading to deterioration in the quality of emergency services, and tending to increase on-floor mortality and morbidity, together with higher overall costs. METHODS: A series of 200 consecutive walk-in patients were interviewed during general practitioners’ office hours. To avoid selection bias, we performed the survey on 31 randomly chosen days, between 11 July 2011 and 31 August 2011, excepting weekends and Thursday afternoons, when GP offices in Bern are closed. The patients were interviewed using a paper based, self-administered questionnaire, which was distributed by a medical student not involved in the medical treatment. RESULTS: 200 patients were interviewed during the study period. The majority of walk-in patients interviewed (82%; n = 165) were registered with a GP. When asked about the circumstances of admission and subjective drivers to visit our emergency department, 39% (n = 61) patients reported greater confidence in the hospital emergency department. When asked if they saw a visit to a GP as appropriate, a majority stated that they preferred the hospital to their GP in any kind of emergency and the majority defined an emergency as either a condition requiring rapid attention or a life threatening situation (53%; n = 63). DISCUSSION: Our study is another small piece of the puzzle to help us to understand why people in “minor” medical emergencies prefer to consult a hospital than their own GP. Our study supported the evidence in current literature that there is a demand for hospital-based ambulatory emergency medicine. Only a future large study on the drivers and barriers to emergency care in Switzerland can provide additional answers.